A novel professional automated auscultatory blood pressure monitor with visual display of Korotkoff sounds: InBody BPBIO480KV validation according to the Association for the Advancement of Medical Instrumentation/European Society of Hypertension/International Organization for Standardization Universal Standard. Issue 2 (14th February 2023) - Ntineri, Angeliki; Theodosiadi, Aikaterini; Menti, Ariadni; Kyriakoulis, Konstantinos G.; Ntousopoulos, Vasileios; Kollias, Anastasios; Stergiou, George S.
Abstract : Objective: A novel automated auscultatory upper arm-cuff blood pressure (BP) monitor (InBody BPBIO480KV) for office use was developed. An electronic stethoscope embedded in the device cuff records the Korotkoff sounds, which are audible to the user and graphically displayed during cuff deflation. Automated BP measurements are provided, while allowing the user to assess the Korotkoff sounds. The device accuracy was tested using the Association for the Advancement of Medical Instrumentation/European Society of Hypertension/International Organization for Standardization (AAMI/ESH/ISO) Universal Standard (ISO 81060-2:2018) and its Amendment 1.2020-01. Methods: Participants were recruited to fulfil the age, sex, BP, arm circumference and cuff distribution criteria of the Universal Standard in general population using the same arm sequential measurement method. Three cuffs of the test device were used for arm circumference 23–28, 28–35 and 33–42 cm. Results: Data from 85 individuals were analysed [mean age 57.3 ± 15.0 (SD) years, 53 men, arm circumference 23–42 cm]. For validation criterion 1, the mean ± SD of the differences between the test device and reference BP readings ( N  = 255) was 0.3 ± 5.5/0.6 ± 4.7 mmHg (systolic/diastolic; threshold ≤5 ± 8 mmHg). For criterion 2, the SD of the averaged BP differences per individual ( N  = 85) was 3.76/3.61 mmHg (systolic/diastolic; threshold ≤6.95/6.91 mmHg). Conclusion: The InBody BPBIO480KV device for office use, which provides automated auscultatory measurements while reproducing and displaying the Korotkoff sounds, comfortably fulfilled the AAMI/ESH/ISO Universal Standard requirements in general population and can be recommended for clinical use. The assessment of Korotkoff sounds by healthcare professionals for evaluating the quality of automated measurements requires further evaluation.